Non-intellective factors associated with students' performance in college physics - Mabutol, Concepcion Bautista (Animo Repository, 1982)
This study determines the association of the students' performance in college physics with selected non-intellective factors. A total of 119 sophomore college students were selected as samples of the study. The transcripts of records of these 119 students were examined to determine the average of their ratings in Physics 21 and Physics 22. An instructor survey was also completed by their respective Physics teachers to complete the information desired for this work. The school year covered was 1980-1981. The chi-square was used in testing the null hypotheses of the study. It was found out that the factors that were significantly associated with students' performance in College Physics are: residential background, study-interest, study-attention, parents' educational attainment and units of Physics earned by Physics teachers in the undergraduate level. The factors that were found not significantly associated with students' performance in College Physics are : type of high school, study-schedule, teaching experience of Physics teachers and units of Physics earned by Physics teachers in the graduate level. On the basis of findings and conclusions, the following recommendations are suggested: 1. Wherever possible, students should stay in the town near the school to be able to devote more time to their studies. 2. Students should develop interest in the study of Physics to be able to develop the correct attitude of inquiry. In introducing Physics, the teachers should make the first few lessons impressing to them to develop proper attitude toward the subject and give them a lasting experience. The introduction should aim to give the students a glimpse of the future of the course and to awaken their interest. 3. Students should pay close attention to their studies in Physics to be able to have a better understanding in the said-course, and 4. Physics teachers should attend Physics classes in the undergraduate level if they have not taken Physics as a major nor minor field of concentration. They can avail themselves of the summer courses in the provincial colleges.